Validity of the acute recovery and stress scale: training monitoring of the german junior national field hockey team - Kölling, S.; Hitzschke, B.; Holst, T.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M.; Foster, C.; Hough, J. (International Journal of Sports Science and Coaching, 2015)
The aim of the present study was to examine the sensitivity of the Acute Recovery and Stress Scale (ARSS). This new psychometric questionnaire was developed to assess the physical, mental, emotional, and overall recovery and stress states of athletes. During a five-day field hockey training camp of the German Junior National Field Hockey Team ( n = 25) the ARSS was administered every morning and evening. The study indicated swift reactions of the scores of the physical and general factors as well as stability of scores for the emotional factors in accordance with the training schedule. The straining effect of the camp was best reflected by the adaptations of the scales Physical Performance Capability (F2.9, 60.3= 10.0, p < 0.001) and Muscular Stress (F4, 84 = 16.7, p < 0.001). The results support the ability of the ARSS to monitor recovery-stress (im-)balances in this sample. Thus, the questionnaire has shown to be a sensitive and practical tool that might be suitable for elite sport settings.